Evaluación del Comportamiento Productivo y Reproductivo de Hembras Bovinas Holstein Friesian, Jersey y Brown Swiss en la Hacienda el Carbón Pillaro - Gutiérrez Montero, José Luis (2018)
The present investigation was carried out in the Tungurahua Province, Píllaro Canton, Marcos Espinel Parish, Tunguipamba neighborhood, located at 2950 meters above sea level, characterized by low temperatures, almost constant throughout the year, abundant and regular rainfall. The project was carried out with the objective of evaluating the productive and reproductive behavior of bovine females Holstein Friesian , Jersey and Brown Swiss in the production of coal "Píllaro". 102 animals were used (42 cows over 5 years, 36 from 3 to 4 years and 24 from 2 to 3 years). Sets production monthly indicators and individual herd averages, were evaluated between January - February 2017 and the number of days of lactation from 2014 to 2017. The average milk production between February and March 2017 was 730 liters per day with values s average per cow per day of 14.6 liters and a price per liter of 0.53 ctvs, value in relation to the quality of the milk. The dairy production for the month of February was 766.42 liters higher than the month of March with 698.2 liters. Comparing the ambient temperature, the month of February of 2017 presented 12.76 ° C and the month of March 11.3 ° C, which determined that the milk production decreased due to the decrease in temperature due to the increase in the hours of darkness. During the period 2014-2017 the days of lactation was 465.2 exceeding the recommended 305 days in a dairy production. The reproductive behavior of the herd and the coal was evaluated based on data from the period 2014-2017. The farm presented animals with a prolonged age at the first service of 22 to 23 months and of first delivery from 33 to 35 months . The interval for the first service, open days, IPP, presented prolonged data because there are more than 3 services per cow caused by a poor detection of heat and fertility problems. While the percentage of fat, protein, is within the ranges allowed by the INEN standards that is 3% fat and 2.9% protein however in the bacterial load count there was a high number of bacteria, which exceeds 50000 CFU recommended by the INEN.